Avoiding surgical site infections in neurosurgical procedures. Issue 3 (1st May 2015) - Fencl, Jennifer L.; Wood, Felecia G.; Gupta, Sat; Swofford, Vangela; Morgan, Melissa; Green, Debbie
<x xml:space="preserve">Abstract</x> For any patient about to undergo a surgical procedure, the possibility of developing a surgical site infection (SSI) is an ever-present risk. SSIs are a true public health concern and their elimination must be a priority for organizations to improve patient safety and the quality of care delivered.